Biomes and ecosystems - Howarth, Robert warren; Mohan, Jacqueline Eugenia (Amenia : Salem press, 2013)
A resource for students and teachers to understand the importance of biomes and ecosystems; to appreciate the study of ecology and how it affects life around the world; to learn of the flora and fauna in biomes and ecosystems; and to initiate educational discussion on the subjects.
Vol.1 1-208p.; Vol.2 209-632p.; Vol.3 637-1028p.; Vol.4 1033-1436p.
Keywords: Indian ocean; Kakadu wetlands; Maldives; Humber estuary